Penerapan Konsep Etika Aritoteles Dalam Pembelajaran: Penerapan Pembelajaran Moral Siswa Kelas III di Sekolah Dasar Palanyar 1, Pandeglang - Sapira, Pini; Desty Endrawati Subroto; Hilma Hilmia; Ilham Adriansyah; Danu Hermawan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article discusses the philosophy of Islamic education and its impact on the application of Aristotle's ethical principles in moral learning for third grade students in elementary schools. Philosophy, derived from the ancient Greek words "philos" (love) and "sophia" (wisdom), has been described by various philosophers such as Plato, Aristotle, and Al Farabi. Education, according to the Indonesian National Education System Law and KBBI, is an effort to develop the spiritual, intellectual, and social potential of individuals. Islamic education aims to change attitudes and behaviors to be in accordance with Islamic values. Various scholars provide views on the philosophy of Islamic education, including analysis of curriculum and teaching methods based on the Qur'an and hadith. The application of Islamic educational philosophy in teaching ethics in elementary schools includes a holistic approach that pays attention to spiritual, emotional, and physical aspects. By integrating this philosophy, it is hoped that students will not only achieve academically, but also become whole individuals and be able to live wisely according to Islamic teachings.